Low frequency, weak MCP‐1 secretion and exhausted immune status of peripheral monocytes were associated with progression of severe enterovirus A71‐infected hand, foot and mouth disease. (17th February 2019) - Pei, X.; Fan, X.; Zhang, H.; Duan, H.; Xu, C.; Xie, B.; Wang, L.; Li, X.; Peng, Y.; Shen, T.
Summary: A minority of hand, foot and mouth disease (HFMD) caused by enterovirus A71 (EV‐A71) results in severe neural complications. However, whether monocyte‐mediated immunity is involved in the disease progression of HFMD remains unknown. One hundred and twenty mild and 103 severe HFMD patients were recruited and enzyme‐linked immunosorbent assay (ELISA), flow cytometry and Transwell culture were performed in the study. Peripheral monocyte counts were lower in both absolute counts and frequencies in severe cases compared to mild cases. After screening 10 monocyte‐related cytokines by ELISA, only monocyte chemoattractant protein‐1 (MCP‐1) was found at higher levels in sera of mild cases compared to those with severe symptoms. Monocytes purified from mild cases produced more MCP‐1 than the cells from severe patients when stimulated in vitro . We observed that immune exhaustion markers programmed death 1 (PD‐1) and programmed death ligand 1 (PD‐L1) were highly regulated on the surface of monocytes from severe cases compared to mild cases. PD‐L1 blockade induced a higher production of MCP‐1 in the supernatant of a Transwell system. The production of MCP‐1 also increased following PD‐L1 blockade of purified monocytes activated by granulocyte–macrophage colony‐stimulating factor (GM‐CSF) combined with R848 or EV‐A71 virus. Our results indicate that absolute count, frequency and levels of MCP‐1 secretion of peripheral monocytes, together with their immune status, probably contribute to differential disease prognosis in EV‐A71‐associated HFMD. Abstract : The main finding of this study is that both absolute counts and frequencies of peripheral monocytes, and level of serum MCP‐1 were lower in severe EV‐A71‐infected cases compared to mild cases. The production of MCP‐1 increased following PD‐L1 blockade of purified monocytes activated by GM‐CSF combined with R848 or EV‐A71 virus. Our results indicate that absolute counts, frequencies and the immune status of monocytes may contribute to differential disease prognosis in EV‐A71‐associated HFMD.